Impact of soft missiles – evaluation of load-time functions. (7th April 2011) - Ruch, D.; Herrmann, N.; Muller, H.S.
The threat spectrum of safety-related structures has severely changed since 11 September 2001. The deterioration capability of large aircrafts impacting on structures has become aware in a dramatic manner. Simplified calculation models for aircraft impact are available but have not been verified for large commercial aircrafts. Based on this background, experimental studies are performed at the Materials Testing and Research Institute (MPA) Karlsruhe of the Karlsruhe Institute of Technology (KIT) to examine the shape and the peak loads of load-time functions induced by an impacting soft missile where the mass and stiffness distribution is similar to a commercial aircraft. The characterisation of the impact phenomena and their variation due to changing test parameters is the goal of these experiments. The experimental set-up, measurement results and their evaluation will be presented. First numerical simulation results will be shown and briefly compared to the prediction using the analytical Riera method.